2010
DOI: 10.1007/s12603-010-0261-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum magnesium and phosphate in older hospitalised patients — Correlation with muscle strength and risk factors for refeeding syndrome

Abstract: Changes in serum magnesium and phosphate levels do not correlate with changes in muscle strength in older hospitalised patients. Risk factors for refeeding syndrome did not predict falls in serum phosphate or magnesium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The incidence of hypophosphatemia in geriatric facilities is reported to range from 14% to 37%. 10 , 30 In a series of patients with gastrointestinal fistula, 3% experienced hypophosphatemia, and in postoperative patients the incidence was 44%. 31 , 32 In patients with hepatic resection, the reported incidence of hypophosphatemia was 100% 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of hypophosphatemia in geriatric facilities is reported to range from 14% to 37%. 10 , 30 In a series of patients with gastrointestinal fistula, 3% experienced hypophosphatemia, and in postoperative patients the incidence was 44%. 31 , 32 In patients with hepatic resection, the reported incidence of hypophosphatemia was 100% 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, low prealbumin or albumin concentration [3,[37][38][39], use of enteral nutrition [3,36,40], and higher amounts of nutritional intake during nutritional therapy [8,31,41] were found to be risk factors. However, some studies did not find that these factors predicted RFS, although some of the studies were small in size with risk for type II errors [37,42,43].…”
Section: Clinical Manifestations Of Rfsmentioning
confidence: 99%
“…Various studies and guidelines have shown a beneficial effect of starting energy intake at a lower rate than generally used, in order to prevent RFS in patients at high risk [12,16,23]. Based on a patient's individual risk for RFS, energy supply should be initiated at lower levels, starting with an initial amount of 5-15 kcal/kg/day, and increased stepwise depending on the laboratory parameters and clinical situation of the patient [8,19,20,23,52,61,62]. The full energy requirements should be met within 5 to 10 days, depending on the prior risk stratification, using a common nutritional macronutrients composition of 40-60% carbohydrates, 30-40% fats, and 15-20% proteins [12].…”
Section: Macronutrientsmentioning
confidence: 99%